Enhancing the LVRT Capability and Mitigation of Power Quality Issues Using UPQC of a Grid Connected Wind Conversion System - C.S Boopathi; Kuppusamy Selvakumar; Avisek Dutta (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
In this paper unified power quality conditioner has been used to enhance low voltage ride through capability of grid connected wind conversion system taking Doubly fed induction generator (DFIG). Unified Power quality conditioner (UPQC) device is a combination of series active filter and shunt active filter. This custom power device is mainly used to mitigate power quality issues which is an essential factor today because of wide application of power electronics devices. UPQC is capable to deal with voltage and current imperfection simultaneously. It is installed in the system mainly to improve the power quality i.e. Voltage sag/swell, Harmonics, reactive power compensation etc. at point of common coupling. System is modeled in MATLAB/SIMULINK and results shows utilization of UPQC for the enhancement of LVRT of a DFIG wind system according to Grid code. when fault occurs in the system, it will create voltage dip and series compensator of UPQC injects during this time to prevent disconnection from grid and stay connected to contribute during fault. UPQC is also used for fast restoration of system steady state, power factor improvement, prevent rotor over current.